Immigration, inequality and income taxes - Mirjam Bächli; Albrecht Glitz (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Immigration may affect income inequality not only by changing factor prices but also by inducing policy makers to adjust the prevailing income tax system. We assess the relative importance of these economic and political channels using administrative data from Switzerland where local authorities have a high degree of tax autonomy. We show that immigrant inflows not only raise gross earnings inequality but also reduce the progressivity of local income taxes, further increasing after-tax inequality. Our estimates suggest that 10 percent of the impact of immigration on the net interquartile and interdecile earnings gaps can be attributed to the political channel.
Keywords: H23; H24; H71; J31; J61; 330; Immigration; Income Taxes; Earnings Inequality